Corporate financial reporting system and developments herein: An exploratory study from Pakistan - Rehana Kouser; Muhammad Abdul Majid Makki; Muhammad Usman Qureshi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
To capture international opportunities of capital accumulation for corporate sector and to contribute in the development of economy, the government of Pakistan acted speedily to harmonize with international financial reporting system immediately after establishment. This study presents a comprehensive detail of Pakistan's adopted efforts along with a critical-eye on developments and improvements in the reporting system with the passage of time. It scrutinizes major milestones in development of the financial reporting framework of Pakistan. We traced financial reporting practices in Indian subcontinent era and found them unsatisfactory. Hindustan was under the colonial power of Great Britain; therefore its impact on accounting and financial reporting in Pakistan was dominant after independence. Examples of this influence are enforcement of companies' act 1913 and auditor's certificate rules shows. We examined the institutional development from establishment of Pakistan till now and divided that era in 1947-1971, 1971-1999 and period of 21stcentury which played vital role in improvement of financial reporting practices in the country. These milestones are established with view of crucial events toward advances in accounting. In early years of Pakistan PIA (Pakistan Institute of Accountants) was first private body but after it ICAP (Institute of Chartered Accountants of Pakistan) made by government was an important step. Next major step was taken in 1971; it was the formation of SECP (Securities and Exchange Commission of Pakistan). Its structure and provisions provided for external reporting of corporations are discussed. Companies' Ordinance 1984 was another beneficial footstep toward this journey. After discussing all the institutional developments and improvements in financial reporting system of Pakistan, we addressed the current status of financial reporting in the 2000s.Study concludes that major improvements and advances made in the financial reporting skeleton are appropriate, will cause improvements in the investor protection, value relevance of accounting information, and will help corporate sector in capital accumulation from international financial markets and will attract cross border investors.
Keywords: 330; Financial Reporting; Framework; Standards; IAS; IFRS; Pakistan; IFRS; Rechtsangleichung; Pakistan